Building resilience in Indonesian agrarian communities: Adaptation strategies and institutional barriers in response to climate change - Setiawan, Aldi Agus (Social Agriculture, Food System, and Environmental Sustainability, 2025)
Background: Climate change has become a real threat to the agricultural sector in Indonesia, with significant impacts on productivity, food security, and the welfare of farmers. Rising global temperatures, shifting rainfall patterns, and extreme climate events have increased the risk of crop failure and reduced the adaptive capacity of agrarian communities. This study aims to examine the adaptation and resilience strategies of agrarian communities in responding to climate change, as well as to identify the structural and institutional barriers they face. Methods: The research employs a qualitative approach with a case study design in several climate-vulnerable areas, including Wonosobo, Bima, and Maros. Data was collected through participatory observations, in-depth interviews, focus group discussions, and document analysis. The Sustainable Livelihood Framework is used to analyze five types of capital that influence farmers' adaptive capacity: natural, human, social, physical, and financial capital. Thematic analysis is applied to explore narrative patterns of farmers' adaptation to climate change. Findings: The findings of this research are expected to contribute to the formulation of community-based adaptation policies and the strengthening of climate-resilient agricultural systems. Conclusion: This study highlights the significant impact of climate change on agricultural livelihoods in Indonesia, while also revealing the adaptive resilience strategies developed by communities through various livelihood assets. Novelty/Originality of this article: This study also highlights the importance of institutional support, adaptive technologies, and the preservation of local wisdom as integral components of strategies to enhance the resilience of agrarian communities in Indonesia.